2021
DOI: 10.1111/acv.12671
|View full text |Cite
|
Sign up to set email alerts
|

Projected climate change threatens Himalayan brown bear habitat more than human land use

Abstract: Climate change and land use change jointly are the largest drivers of population declines, range contraction and extinction for many species across the globe. Wide‐ranging and large‐bodied species are especially vulnerable to habitat loss and fragmentation due to their typically low population densities, reflecting their need for extensive and connected habitats. We used the multi‐scale Random Forests machine learning algorithm to identify factors driving the habitat selection and future changes in habitat of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 104 publications
(152 reference statements)
2
21
0
Order By: Relevance
“…Our results are consistent with similar studies arguing that habitat selection measured at one specific scale may be insufficient to predict that selection at another scale (Mayor et al 2009). Similar studies for brown bears (Martin et al 2012;Sánchez et al 2014); Dar et al 2021) and other species (Shirk 2012;Shirk et al 2014;Wan et al 2017;Klaassen and Broekhuis 2018) also support the scale-dependent habitat selection. Consistent with these studies, our results indicate that habitat selection occurs across the range of scales for sloth bears, thus supporting our hypothesis of scale-dependent habitat selection in sloth bears.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are consistent with similar studies arguing that habitat selection measured at one specific scale may be insufficient to predict that selection at another scale (Mayor et al 2009). Similar studies for brown bears (Martin et al 2012;Sánchez et al 2014); Dar et al 2021) and other species (Shirk 2012;Shirk et al 2014;Wan et al 2017;Klaassen and Broekhuis 2018) also support the scale-dependent habitat selection. Consistent with these studies, our results indicate that habitat selection occurs across the range of scales for sloth bears, thus supporting our hypothesis of scale-dependent habitat selection in sloth bears.…”
Section: Discussionsupporting
confidence: 91%
“…Habitat features such as forest cover, terrain heterogeneity, and human population density were reported to be influential on a large scale (Puri et al 2015). A similar multi-scale distribution assessment using the random forest algorithm was attempted for Himalayan brown bears (Ursus arctos isabellinus) across their range in Himalayas (Dar et al 2021). The study showed that habitat selection in brown bears was scale-dependent and brown bears perceived the habitat features across multiple spatial scales.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason behind the comparatively less contribution of land use change in predicted habitat decline is possibly because a majority of alluvial floodplain has already been converted into croplands. Similar studies conducted in India and Nepal for Asian elephant and Himalayan brown bear also suggested that the likely effects of climate change on habitat decline is greater than human land use changes (Dar et al, 2021 ; Kanagaraj et al, 2019 ).…”
Section: Discussionmentioning
confidence: 72%
“…Our ensemble approach identified suitable rhinoceros habitat that was mainly concentrated in the central and western lowland of Nepal, indicating that its distribution was constrained by topographic variables. Suitable habitat ranges of many terrestrial species have shifted toward higher elevations in response to changing climate (Chen et al, 2011 ; Dar et al, 2021 ; Moritz et al, 2008 ). Rhinoceros habitat suitability is limited by topographic factors given that slope contributed strongly to our models (Figure 4e ).…”
Section: Discussionmentioning
confidence: 99%